Internet usage patterns and preferences- A study of youngsters in Northern India - Gurleen, Kanwal; Sukhmani, (Gyan Management Journal, 2012)
The internet has brought a transformation in many aspects of life. ft is one of the biggest contributors in making the world into a global village. Use of internet has grown tremendously since it was introduced. It is mostly because of its f1exibility. The internet has developed to give many benefits to mankind. The access to information is considered to be one of the most important Researchers can have access to libraries around the world. Some charge a fee but most provide free services. Earlier, a person had to spend hours and hours in the libraries but now at the touch of a button one can access ah uge data base.
Keywords: World Wide Web; VOiP; IPTV; online shopping